MULBERRY LEAVES: THE TREASURE OF MICRONUTRIENTS - Srivastava, Sarita (Indian Journal of Community Health, 2015)
Mulberry tree, a plant of the family of Moracaea and genus Morus, has been widely cultivated to feed silkworm. It is a fast growing deciduous tropical plant.it is grown extensively for raising silkworms. Sericulture based agro forestry has great potential to generate large income in India. In addition to sericulture, mulberry has a wide and diverse potential to protect environment in varying agroclimatic conditions. Mulberry can be grown as a tree as well as in combination with agricultural crops(intercrop) to increase per unit area production (Kant et al., 2004).